STUDENTS' INTEREST IN INVESTING IN THE CAPITAL MARKET AFTER THE PANDEMIC - Nur Afni Hidayahti; Suwarno Suwarno (Sean Institute, 2022)
This research was conducted to examine the effect of investment knowledge, investment benefits, investment motivation, minimum investment capital and investment return on investment interest in the post-pandemic capital market among active students studying accounting and management in the city of Gresik. This type of research is associative with quantitative methods. This study uses primary data from questionnaires and is measured using a Likert Scale. Based on the existing criteria, 100 economic and business faculties were sampled in this study, namely 67 students majoring in accounting and 33 students majoring in management. Data were analyzed using Partial Least Square (PLS). The data in this study were collected using a questionnaire and then processed using the SmartPLS 3 program. The results showed that the coefficient of investment benefits and investment motivation was positive but did not have a significant effect, other variables such as investment knowledge, minimum capital investment and return on investment had a positive and significant effect.